Assessment of The Effects of Edentulousness on Temporomandibular Components by Using Cone Beam Computed Tomography - Arıkan, Büşra; Dedeoğlu, Numan; Duman, Şuayip Burak (UI Scholars Hub, 2022)
Objective: The aim of this study is to evaluate the effects of edentulousness on the temporomandibular joint using cone beam computed tomography (CBCT). Methods: In this study, CBCT images were evaluated in a total of 48 patients (24 dentulous, 24 edentulous). Ninety-six temporomandibular joint CBCT images were examined. Eminence inclination, condyle head widths and joint space were measured and statistically compared between the edentulous and dentulous groups. Results: The articular eminence inclination value the mediolateral width of the condyle and the anteroposterior width of the condyle were found significantly higher in the dentulous group than in the edentulous group. There was no significant difference between the dentulous and edentulous groups in terms of the anterior, superior and posterior joint space. Conclusion: In the edentulous patients, the articular eminence inclination value, mediolateral and anteroposterior widths of the condyle head were found to lower in comparison to the dentulous patients.